Perancangan Pintu Ruang Start Arena Pacuan Kuda Menggunakan Sistem Pneumatik - Amri Hidayat; Aldrin Aldrin (Politeknik Negeri Padang, 2022)
Starting gate door is a tool used horse racing arena that serves as a star or space to take off before darting run to racetrack. Doors starting gate consists of a variety of forms and working method, from the manual to which use the automatic system, such as; mechanical, hydraulic, electric and pneumatic systems. Starting gate door with pneumatic system is a tool that is used to open and close starting gate door, the way it works is that a pneumatic cylinder is installed on the door, then pneumatic system functions to open and close the door. Pneumatic system is a tool that uses air as an energy source, components required in the pneumatic system: compressor or air supply unit, or air processing unit (Filter, regulator, and lubrication), regulator or valve unit and the main thing is the pneumatic cylinder serves as a tool which converts compressed air energy into mechanical energy (linear motion of the cylinder rod). In this study aims to be able to get the shape of the starting gate door using a pneumatic system, which can be used as a reference in making the actual door, so that in its application on the racetrack it can be used easily and the time it takes to release the horse becomes faster and the time it takes to release the horse becomes faster. From design results, it is known load that will work on the pneumatic cylinder is 4703.5 N, the inner diameter 100 mm, diameter cylinder rod is 25 mm, total air consumption required is 4,6 liter, compressor discharge is 0,39 liter/second, and compressor power is 0,5 HP.